Analogies on the legal protection for singers and songwriters in Colombia, France, and the United States of America - Palacios Olaya, Laura Camila (Scientific journal of social studies, 2025)
This article analyzes from a legal perspective the laws that protect songwriters and singers on their intellectual property rights: specifically, the rights of authors and neighboring rights found in Colombian and French legislations, as civil law descendants, contrasting such findings with the the U. S. Legislation on Copyright, as a system that follows the common law tradition. Then, the text addresses copyright and fundamental rights of authors to the light of Colombian Constitutional Court’s decisions, and the European Union’s 2019/790 Directive on Copyright and related rights in the Digital Single Market. Up next, the article warns about the limits to Copyright, concluding with how important collective management is to protect the interests of authors and performers. All previous points are analyzed from a comparative, qualitative, documental, legal research-based method, to identify prerogatives protecting copyright owners (such as artists, composers and authors), understanding copyright and neighboring rights as essential elements to protect authors and artists, and promoting culture, creativity and entertainment.